PENGEMBANGAN BAHAN AJAR E-BOOK PADA MATA KULIAH PENGEMBANGAN MEDIA FOTO PRODI TEKNOLOGI PENDIDIKAN FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI MAKASSAR - Putri Nursadrina Hiwan; Abd Hakim; Farida Febriati (STKIP Subang, 2023)
Educational Technology is one of the study programs on the Makassar State University campus. Educational Technology has a photo media development course handled by Dr.Abdul Hakim S.Pd., M.Sc. as a course lecturer. The existence of photo media courses is currently not supported by the existence of teaching materials which are used as permanent reference materials by lecturers in the photo media learning process so that researchers are motivated to carry out research on developing teaching materials in the form of e-books. This research aims to 1) Identify the level of need for developing teaching materials in the form of E-Books in photo media development courses. 2) Measuring the level of validity of teaching materials in the form of E-Books in photo media development courses. 3) Measuring the level of practicality of teaching materials in the form of E-Books in photo media development courses. This research was carried out using an R&D (Research and Development) approach or development research that produces a product. This research was developed using the Thiagarajan model with 4D stages (Define, Design, Development, Disseminate). This research was conducted within the Educational Technology Study Program FIP UNM. The subjects of this research who were selected by random sampling were active students of the educational technology study program with details: 10 students for small group trials and 30 students for large group trials. Data collection in this research used interview methods, needs identification questionnaires, media expert validation questionnaires, content/material expert validation questionnaires, small group trial questionnaires, large group trial questionnaires, and supporting documentation in the form of photographs. The data analysis method consists of qualitative descriptive analysis and descriptive statistical analysis. The research results showed that: the teaching materials in the form of E-Books that were developed were at the required level; The teaching materials developed are material related to photo media development courses which are arranged in the form of an E-Book application; product feasibility based on content/material expert validation with very good results, and media validation with very good results, small group trials with good results, large group trials with results in the good category and the product developed is in the valid and practical category and can be used.